Clinical topics in cultural psychiatry - Bhugra, Dinesh (Colección de libros electrónicos de ULoyola, 2010)
Cultural factors play a very important role in the way psychiatric symptoms are presented to clinicians and how clinicians deal with them. This book offers practical advice on the topic for the individual mental health practitioner. It provides an overview of cultural factors in the causation and management of mental health problems and an introduction to cultural competency training for healthcare professionals (now required for all National Health Service staff by the Department of Health).